PERSEPSI WISATAWAN TERHADAP WISATA HERITAGE (STUDI KASUS PADA LIMA DESTINASI WISATA HERITAGE DI KOTA MEDAN) - Abdul Rahman; Elok Perwirawati (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2022)
The purpose of this study was to determine tourist perceptions of five heritage tourist destinations in the city of Medan, namely the Lonsum Building, Tjong A Fie Mansion, Maimoon Palace, the Great Post Office, and the Al-Mahsun Mosque. The approach or research method used in this research is descriptive quantitative survey method which aims to analyze and explain the causal effect between independent and dependent variables through hypothesis testing. From the results of the study, it can be concluded that the perception of tourists visiting five heritage tourist destinations in Medan City, the majority gave a positive response both in terms of marketing, accessibility, destination attractiveness, to human resources. even if there is a negative perception only a small part of it as part of the evaluation for managers and related agencies. This can be seen from the exposure of the single table that the researcher has included in this thesis